CHEMICAL COMPOSITION OF PANICUM MAXIMUM AS AFFECTED BY PIG MANURE RATES, PLANTING METHODS AND HARVESTING STAGES IN THE NORTHERN GUINEA SAVANNA OF NIGERIA. (FUDMA JOURNAL OF SCIENCES, 2020)
Effects of Pig manure application, planting methods and harvesting stages on chemical composition of Panicum maximum were evaluated during the rainy season of 2018 at the Feed and Nutrition Research Program of the National Animal Production Research Institute, Shika, Zaria, Nigeria. The experiment was laid in a Split Plot Design with 4Ã—2Ã—3 factorial arrangement replicated three times. The manure rates were 0, 5, 10 and 15t/ha, planting methods were; drilling and broadcasting methods while the harvesting stages were 6, 9 and 12 weeks after planting. The results indicated a higher (P
Keywords: Forage, manure, mineral, sampling, sowing